STRATEGI BERTAHAN PEDAGANG PASAR DI MASA PANDEMI COVID 19 DI TELUK KUANTAN KABUPATEN KUANTAN SINGINGI - Nadya Clarissa Arlin; Siti Sofro Sidiq (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2022)
This research was conducted in the Defense Strategy of Traditional Market Traders During the Covid 19 Pandemic In Teluk Kuantan, Kuantan Singingi Regency. This study uses descriptive qualitative research methods. In collecting data using observation research methods, explore and also documentation. Traditional market traders and survival strategies carried out during the covid 19 pandemic. In the midst of covid 19 which has an impact on various people's lives, both socially and economically, those who also feel the impact of the pandemic are informal sector actors, one of which is small traders in traditional markets. Traditional markets are a major concern amid the development of modern markets and the existence of traders' markets in surviving the changes due to the COVID-19 pandemic is very important. Keyword: Market, Trder, Traditional Market in Kuantan